AMATEUR SURFING ON THE SOUTH COAST OF SÃO PAULO: LIFESTYLE AND WORK AS FACTORS FOR PRACTICE ENGAGEMENT - Luiz Carlos Marinovic Doro; Vinícius Demarchi Silva Terra; Império Lombardi Junior (Journal of Physical Education, 2022)
ABSTRACT The present study addresses correlations between lifestyle and engagement in physical activity, in addition to discussing the conditions that make it possible for amateurs to continue with a complex practice such as surfing for a long time. To this end, we interviewed eleven surfers with more than ten years of uninterrupted practice on the south coast of São Paulo. Using content analysis, it was possible to find that their permanence is less influenced by matters of gender, age and marital status (usually prioritized in the literature on the topic) than by employment conditions. It is argued that engagement in surfing is linked to the lifestyle and ideals of youth, while the conditions that lead amateurs to keep this practice involve family and employment relationships, the stability of which provides security to routine and modulates the games between social and nature times. Thus, mature surfers narrate a way of living that values prudent attitudes as a means for re-signifying surfing in their lives, pointing to a transformation of the surf culture. It is considered that the relationships between permanence in practice and job stability are worth investigating in further studies.